Taking care of everyone's business: interpreting Sicilian Mafia embedment through spatial network analysis. Issue 2 (3rd April 2022) - Battisti, Michele; Lavezzi, Andrea Mario; Musotto, Roberto
ABSTRACT: Mafia-type organisations often have a strong geographical and cultural entrenchment in the territory they belong. However, their analysis as a spatially networked social structure is still missing. A combined socio-spatial network analysis is presented here, through the demise of a large police operation called Operazione Perseo in 2008. This approach is developed in two ways. At first, a visual representation of the social network of this large group of mafiosi embedded in a geographical space is presented. Three main salient territorial features of the network are thus highlighted. A high density of links in some neighbourhoods, as well as connections across different Mandamenti, the territorial units where Mafia families operate, and the correlation of links and socio-economic determinants, like the unemployment rates. Secondly, a spatial econometric analysis of centrality measures of the group is suggested here. Findings show a positive spatial correlation in the Eigenvalue centrality scores.